2010
DOI: 10.1002/dneu.20775
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of serotonin 5‐HT4 receptors in the mouse developing thalamocortical projections

Abstract: The serotonin 5-HT(4) receptor (5-HT(4)-R) is an unusually complex G-protein coupled receptor that is likely to play important roles in brain development and that may underlie the comorbidity of central and peripheral abnormalities in some developmental disorders. We studied the expression of 5-HT(4)-Rs in the developing mouse forebrain at embryonic days 13, 15, 17, and at postnatal days 3 and 14 by using immunohistochemistry, tract tracing, and quantitative RT-PCR. The developing thalamocortical projections t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…We have previously shown that the thalamocortical projections express 5-HT 4 -Rs in the embryonic mouse brain [Slaten et al, 2010]. However, it is unlikely that the observed upregulation was due to an increase in the mRNA levels in thalamocortical neurons, since our samples did not include the diencephalon and long-projection axons typically do not contain mRNA [Vilaro et al, 2005].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We have previously shown that the thalamocortical projections express 5-HT 4 -Rs in the embryonic mouse brain [Slaten et al, 2010]. However, it is unlikely that the observed upregulation was due to an increase in the mRNA levels in thalamocortical neurons, since our samples did not include the diencephalon and long-projection axons typically do not contain mRNA [Vilaro et al, 2005].…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown that 5-HT 4 -Rs and ␤ 2 -ARs may play important roles in the neurobiology of depressive disorders [Mongeau et al, 1997;Sastre et al, 2001;Duman, 2007;Lucas et al, 2007;Tamburella et al, 2009], Alzheimer's disease [Lezoualc'h, 2007;Yu et al, 2008Yu et al, , 2010, and autism spectrum disorders [Connors et al, 2005;Cheslack-Postava et al, 2007;Janušonis, 2008;Vincent et al, 2009;Slaten et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Slaten et al . () reported that 5‐HT4 receptor is transiently expressed in the mouse developing thalamocortical projections from E13 to E17. While these studies described a spatiotemporal pattern of 5‐HT receptor expression in the developing brain, there is a paucity of information regarding cellular localization of these receptors.…”
Section: Discussionmentioning
confidence: 99%